Peningkatan Hasil Belajar Tematik Terpadu Siswa Menggunakan Model Problem-Based Learning di Kelas III Sekolah Dasar - Ariani, Vennisa; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The low student learning outcomes in integrated thematic learning, the researchers conducted this research. Teachers are still unable to carry out the learning process using the PBL model properly and optimally. This has an impact on student learning outcomes. In order to improve the learning outcomes of elementary school thematic learning, this study tries to describe how the PBL model is used in the learning process. PTK is a type of research combining qualitative and quantitative methods. There are two cycles for this research, there are four stages, namely: planning, implementation stage, observation stage, and reflection stage. The research data were obtained from observations of the learning process, tests in the form of evaluation sheets carried out by students, and non-tests taken from observations of students' attitudes. The results of the RPP assessment for cycle I were 85% and cycle II were 94% with good and very good qualifications. The results of the assessment of the observation of the aspects of teachers and students in the first cycle were 83% with good qualifications and 93% in the second cycle with very good qualifications. In conclusion, the use of the PBL model can increase learning outcomes in elementary schools